Indian Insurance Sector : A Study Of Challenges And Opportunities Offered By Recessionery Forces (Trinity Journal of Management, IT & Media (TJMITM), 2012)
The global economy is still perplexed with the impact of the  recession which started with the sub-prime crisis in the  United States and found its way to other developed and  emerging economies of the world. The financial meltdown  has definitely cast a deep shadow over the Indian financial  sector, most significantly the insurance arena which is still  not 'recession-proof. Economic growth spurs insurance  activities and recession creates manifold problems for the  insurance mechanism. Indian Insurance industry follows  closely the fortune of the financial sector and is directly  influenced by the movements at the macro-economic  level. Continued depressed market and resultant decline  in premium volumes (and consequently reduced profits) is  likely to put pressure on the management of Indian  insurance companies. Yet, despite the slowdown, the  performance of the Indian insurance sector has shown  consistent improvement. With the liberalization of the  financial sector in India, the entry of new private players in  the Indian insurance segment has helped accelerate the  pace of capital deployment. The present study focuses on  the stand of Indian insurance industry amidst economic  crisis and the unequivocal impact of recession shaping the  future of the insurance business in India.
Keywords: Insurance; Liberalization; Recession